Satellite Imagery - A Tool of Diversified Applications in Exploration and Development of Oil and Gas Fields - Siddiqui, N. K. (Journal of Himalayan Earth Sciences, 1997)
Pakistan Petroleum Ltd (PPL), amongst the pioneers for exploration and development of oil and gas fields in Pakistan have an extensive/historical data-base. The off-the-shelf availability of satellite imagery, since late seventies, not only expanded our data-base quickly but provided a powerful tool of diversified applications. The spectral, spatial and temporal resolution of satellite imagery has since been used for applications as diversified as: Geological mapping in exposed areas and anticipated subsurface structures. Lineaments/topographic anomalies in plains. Identification of suitable geological sections and their approach for stratigraphic measurements. Monitoring of river channels/water bodies for carrying out field development/ drilling operations. Planning of geophysical surveys and layout of the seismic lines to be recorded. Mosaic of the entire country for better understanding of geology/tectonics etc. and the spatial relationship of different sedimentary basins in Pakistan.